Topical Ranibizumab inhibits inflammatory corneal hem- and lymphangiogenesis - Bucher, Franziska; Parthasarathy, Anand; Bergua, Antonio; Onderka, Jasmine; Regenfuss, Birgit; Cursiefen, Claus; Bock, Felix (Acta Ophthalmologica, 2014)
Purpose: Ranibizumab (Lucentis(®) ) is a Fab-Fragment of a recombinant, humanized, monoclonal VEGF (anti-vascular endothelial growth factor) antibody. This study analyzed the ability of topical Ranibizumab to inhibit lymphangiogenesis in addition to hemangiogenesis after acute corneal inflammation in vivo. In addition, the effect of Ranibizumab on the proliferation of human lymphatic endothelial cells (LECs) and blood endothelial cells (BECs) in vitro was studied. Methods: The inhibitory effect of Ranibizumab on LECs and BECs was studied in vitro using a proliferation enzyme-linked immunosorbent assay (ELISA) assay. To study the in vivo effects of Ranibizumab, the mouse model of suture induced inflammatory corneal neovascularization was used. Study mice received topical Ranibizumab as eye drops. After 1 week excised corneas were stained with LYVE-1 and CD31. Hemangiogenesis and lymphangiogenesis were analyzed morphometrically by using a semiautomatic method based on the image analyzing program Cell^F. Results: An antiproliferative effect of Ranibizumab was seen in vitro on both human BECs and LECs with a significance of p < 0.0001 and p < 0.0004, respectively. In vivo experiments showed that topical application of Ranibizumab significantly inhibits both hemangiogenesis (p = 0.0026) and lymphangiogenesis (p = 0.0026) in the cornea. Conclusion: Ranibizumab is a potent inhibitor of inflammatory corneal hemangiogenesis and lymphangiogenesis in vivo with a direct inhibitory effect on both endothelial cell types in vitro. This study for the first time demonstrates an inhibitory effect of Ranibizumab on lymphatic vessels which could have a wider range of clinical applications.
EVALuna2:21062